Global Research Perspective on Household Food Waste Prevention (Chinese and English versions) - Méndez Lazarte, Christiam (2025)
Food waste remains a pressing global challenge, with households as major contributors. Understanding its key drivers is essential for fostering sustainable consumption practices. This study employsa bibliometric analysis, using co-occurrence and co-citation networks, to map the evolution of research on household food waste prevention, identifying key themes and influential works. The co-citation analysis reveals three major research clusters: (1) food ecosystems, (2) supply chains and measurement, (3) the expanded Theory of Planned Behavior and complements in explaining the psycho-social factors influencing household food waste. Findings indicate a shift in research focus from waste management toward prevention, emphasizing policy interventions, behavioral nudges, and consumer awareness. This study contributes to the sustainability discourse by identifying critical research gaps and future directions for more effective food waste prevention. Through mapping the intellectual landscape of food waste research, this work offers valuable insights for policymakers, researchers, and practitioners seeking to minimize household food waste.